The Boma: Livestock are a vehicle for a better world - International Livestock Research Institute (International Livestock Research Institute, 2022)
Susan MacMillan knows why livestock matter. An ILRI Emeritus Fellow, she has led public awareness and advocacy communications at ILRI for nearly 33 years. In the latest episode of The Boma, Elliot Carleton and Brenda Coromina find out how Susan went from being an Ohio native who had never even glimpsed a living cow, to becoming one of the most passionate advocates for livestock farming in developing countries today. In a wide-ranging and informative talk she explains how the modern stigma against livestock farming in some countries was born from good intentions, her respect for vegetarians and vegans, and why livestock matter for countless people in the world today and tomorrow. Listen to the episode to find out what Susan thinks the future of livestock will look like. And listen to Susan Macmillan and Lora Iannotti go deeper into the nutritional benefits of livestock-derived foods in Season 1 Episode 6 of The Boma: 'Animal-source foods for people and the planet'.